Marketing Mix, Motivation, and Attitude Correlation Towards Purchase Intention in Rural Tourism - Sri Wahyuni; Atik Aprianingsih (University of Merdeka Malang, 2025)
Experiential nature-based tourism has become a hype after the COVID-19 pandemic. Nonetheless, not every special interest tourism provider like SAREMA in Garut is able to ride this wave. Therefore, this research is going to unveil the conventional 7Ps Marketing Mix and psychological aspect to analyze the most dominant factor in driving customers’ decisions in this niche market segment. The study is constructed using a quantitative method by utilizing survey data from 210 respondents using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test a mediation model. The bootstrapping result was that the Product, Place, Promotion, People, and Process had no positive correlation towards Customer Attitude. Meanwhile, Price, Physical Evidence, Push Motivation, and Pull Motivation show positive correlation. Through this analysis, it is proven that Customer Attitude is still relevant as the highest and strongest mediator (O = 0.711, ρ = 0.000) of Purchase Intention. This research show that service products like tourism cannot solely rely on traditional 7Ps as their marketing strategy methods. However, the 7Ps remain as ‘hygiene factor’ (a primary antecedent to prevent customers’ dissatisfaction) while the psychological constructs (Push and Pull Motivation) need to be captured in the marketing strategy to increase the destination’s attractiveness.